Growth of Beauveria bassiana combined with MIPC Insecticide and its efficacy to control the brown planthopper Nilaparvata lugens - Aminudin Afandhi; Yayan Atma Kunjana; Fery Abdul Choliq; Amin Setyo Leksono (Research Journal of Life Science, 2020)
The objectives of this study were to evaluate the efficacy of MIPC to control the brown planthopper Nilaparvata lugens, one of the most damaging pests of rice in the field and determine the effect of various of its doses on the growth of the fungus B. bassiana. The research was carried out in a rice field and in the Biological Agents Development Laboratory, Department of Pests and Plant Diseases, Faculty of Agriculture, Brawijaya University, Indonesia. The field efficacy test of the MIPC insecticide was conducted by applying 0.5-, 1.0-, 1.5-, and 2.0-kg/ha doses. The insecticidal compatibility test of MIPC with B. bassiana was conducted in 0.5-, 1.0-, 1.5-, and 2.0-g/L doses of MIPC. Application of MIPC insecticide at 0.5-, 1.0-, 1.5-, and 2.0-kg/ha doses had no significant difference in reducing N. lugens population in the vegetative phase (28 to 70 days after planting). The MIPC doses of 1.0, 1.5, and 2.0 g/L were highly toxic or incompatible with the growth of B. bassiana. Meanwhile, a sublethal concentration of MIPC insecticide of 0.5 g/L was non-toxic to B. bassiana. Therefore, this study recommends the use of 0.5 g/L MIPC combined with B. bassiana fungi.